Emergency care of a patient with ventricular arrhythmiastorms following acute myocardial infarction (1例急性心肌梗死后并发室性心律失常电风暴患者的急救护理) - WANG Biyun (汪碧云) (Association of Integrative Nursing, 2023)
This paper summarized the emergency care of a patient with ventricular arrhythmiastorms following extensive anterior wall ST-segment elevation myocardial infarction. The timely and effective rescue measures, illness condition observation and recording, mild hypothermia therapy and related specialized nursing, basic nursing and individualized psychological care are of great importance to the successful rescue and improvement of prognosis. (本文总结1例广泛前壁急性ST段抬高型心肌梗死后并发室性心律失常电风暴患者的急救护理体会。护士及时有效的抢救配合、严密的病情观察和记录、亚低温治疗专科护理、扎实的基础护理、人性化的心理干预等, 对成功救治患者和改善预后等有着重要意义。)